Relevant Species Selection for Preclinical Safety Studies of Medicines: A Review - G. N. Engalycheva; R. D. Syubaev (Безопасность и риск фармакотерапии)
INTRODUCTION. The use of relevant species of laboratory animals in preclinical safety studies during the development of novel medicines provides valuable information for assessing the risks and benefits of such medicines for humans. The appropriate species are selected upon consideration of scientific, ethical, and practical aspects, and the choice should be justified. Regulatory documents of the Eurasian Economic Union (EAEU) indicate that preclinical safety studies of medicines should use relevant species of animals, but the recommendations for their choice are insufficient. Therefore, it is essential to analyse information from international regulatory documents on preclinical studies and recommendations from the scientific community to identify meaningful criteria that can be used to select experimental animals for preclinical studies.AIM. This study aimed to analyse the current regulatory, scientific, and methodological framework in order to identify key factors and criteria for substantiating the choice of relevant species of experimental animals for preclinical safety studies.DISCUSSION. This article analyses guidelines on preclinical studies issued by the EAEU, the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH), and the European Medicines Agency (EMA), as well as scientific publications on selecting experimental animals. The findings suggest that the most comprehensive recommendations for selecting relevant animals are provided in the EAEU Rules for conducting studies of biological medicinal products as well as the ICH S6(R1) guideline, the ICH S5(R3) guideline on reproductive toxicity studies, the ICH S11 guideline on the development of paediatric pharmaceuticals, and the EMA guideline on strategies to identify and mitigate risks of the first-in-human use of medicinal products. Selecting suitable animals for preclinical studies has been a subject of lively scientific debate. According to research sponsors, the most common regulatory requests related to animal relevance are to provide additional information on the pharmacological relevance of the selected species, to justify the use of only one species, or to conduct additional studies in other species. Many research teams use internal documents that describe the stages and criteria that facilitate the selection of relevant experimental animals. The scientific community has offered over 40 different parameters that, when assessed in vitro, in vivo, and in silico, can help researchers justify the relevance of experimental animals for preclinical safety studies.CONCLUSION. Selecting relevant test systems and models for preclinical safety studies is a scientific endeavour in its own right. To justify the relevance of experimental animals, ensure the translatability of results, and comply with ethics principles, the most valuable criteria are the criteria developed using a systemic approach based on in vitro and in vivo analysis of a set of pharmacodynamic, pharmacokinetic, and toxicological parameters.